2021
DOI: 10.1111/joa.13435
|View full text |Cite
|
Sign up to set email alerts
|

Automated analysis of rabbit knee calcified cartilage morphology using micro‐computed tomography and deep learning

Abstract: This is an open access article under the terms of the Creative Commons Attribution License, which permits use, distribution and reproduction in any medium, provided the original work is properly cited.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 49 publications
0
18
0
Order By: Relevance
“…12 To detail further changes in the subchondral bone plate, a highresolution µCT is needed to separate the subchondral bone plate porosity and calcified cartilage. 38 The OARSI score in the medial tibial plateau was greater in the CNTRL group compared to the C-L and ACLT groups at the 2-week time point. We can only speculate that this may be ascribed to the presence of spontaneous OA in the CNTRL group at the beginning of the experiments.…”
Section: Discussionmentioning
confidence: 80%
See 1 more Smart Citation
“…12 To detail further changes in the subchondral bone plate, a highresolution µCT is needed to separate the subchondral bone plate porosity and calcified cartilage. 38 The OARSI score in the medial tibial plateau was greater in the CNTRL group compared to the C-L and ACLT groups at the 2-week time point. We can only speculate that this may be ascribed to the presence of spontaneous OA in the CNTRL group at the beginning of the experiments.…”
Section: Discussionmentioning
confidence: 80%
“…The resolution of the µCT imaging we used was moderate and was selected to allow comparisons to our previous studies 12 . To detail further changes in the subchondral bone plate, a high‐resolution µCT is needed to separate the subchondral bone plate porosity and calcified cartilage 38 …”
Section: Discussionmentioning
confidence: 99%
“…[28][29][30] Recently, emerging studies showed that AI can be used in orthopaedics. [31][32][33] For example, Yeh et al 30 showed that an AI-baed automatic alignment measure system can locate spinal anatomic landmarks with a high accuracy and produce radiographic parameters that correlated well with operator-based measurements. Yabu et al 34 also demonstrated that convolutional neural network could detect new osteoporotic vertebral fractures utilising magnetic resonance images with performance comparable to that of spine surgeons.…”
Section: Discussionmentioning
confidence: 99%
“…Deep learning and speci cally convolutional neural networks (CNNs) have recently seen an enormous increase in popularity for their application in di cult biological micro-CT image segmentation tasks 49 . CNN has been recently used for segmentation of: ant brain 50 , murine mineralised cartilage/bone 51 and rabbit calci ed knee cartilages 52 in micro-CT images. While this segmentation provides us with morphological information about the object of interest, it does not tell us anything about its function in the context of brain anatomy.…”
Section: Introductionmentioning
confidence: 99%